Historical Geography, feminist research and the gender politics of the present. Issue 9 (20th July 2018) - Moore, Francesca
Abstract: It is thirty years since the first call to engage with gender as an analytical category was made in the sub‐discipline of Historical Geography. Significant advances in scholarship have been made in this time, particularly the re‐situation of women in the history of Geography as a subject. This paper looks to the next thirty years in Historical Geography and asks how the sub‐discipline can retain and develop its critical political edge. In the 2017 Women's Marches protestors dressed as suffragettes from the early twentieth century and proclaimed that little had changed in the fight for women's rights. Taking this 'Victorian present' as a starting point, this paper explores ways to connect Historical Geography to the gender politics of the present. The paper argues that the sub‐discipline has the methodological tools to use the past as a form of female power to engage with the inequalities that women still face. A sketch of a feminist historical geography of the present is provided using emancipatory and participatory research tools.